2016
DOI: 10.1371/journal.pone.0161710
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Subtypes. Transitions over Time

Abstract: BackgroundAlthough subtypes of chronic obstructive pulmonary disease are recognized, it is unknown what happens to these subtypes over time. Our objectives were to assess the stability of cluster-based subtypes in patients with stable disease and explore changes in clusters over 1 year.MethodsMultiple correspondence and cluster analysis were used to evaluate data collected from 543 stable patients included consecutively from 5 respiratory outpatient clinics.ResultsFour subtypes were identified. Three of them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…The selection of number of clusters was done a priori based on clinical judgement and previous reports, representing the different domains of the disease: age, symptoms, exercise capacity, quality of life and airway obstruction. The present study findings confirmed those from Esteban et al . giving further longitudinal reproducibility to a technique that is becoming more popular for the identification of common clinical characteristics in COPD patients …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The selection of number of clusters was done a priori based on clinical judgement and previous reports, representing the different domains of the disease: age, symptoms, exercise capacity, quality of life and airway obstruction. The present study findings confirmed those from Esteban et al . giving further longitudinal reproducibility to a technique that is becoming more popular for the identification of common clinical characteristics in COPD patients …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the present study findings are similar to the ones from Esteban et al 12 who also found that approximately 28% of their large population of stable COPD patients migrated to another cluster the year after, although there are differences in the study population and in the time of follow-up between the two studies. The present study population included patients from several Spanish centres, who were younger, had less degree of airway limitation and most importantly were followed up for a longer period of time.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations